2022
DOI: 10.1007/s00103-022-03598-9
|View full text |Cite
|
Sign up to set email alerts
|

Seltene Erkrankungen in den Daten sichtbar machen – Kodierung

Abstract: ZusammenfassungSeltene Erkrankungen (SE) werden durch die im deutschen Gesundheitssystem verwendete Diagnosenklassifikation ICD-10-GM (International Statistical Classification of Diseases and Related Health problems, 10th Revision, German Modification) nur zu einem kleinen Teil eindeutig erfasst. Daher sind Aussagen zur Häufigkeit von SE sowie zum speziellen Versorgungs- und Finanzierungsbedarf nicht möglich, was zu einer lückenhaften Datenlage als Entscheidungsgrundlage für Krankenkassen, Leistungserbringer u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, a more comprehensive coding for inpatients represents an important step towards obtaining improved epidemiological data on rare diseases. 5,13 It would be interesting to determine whether the prevalence data from the Orphanet Epidemiology File aligns with the coded cases of rare diseases or whether an update to the Epidemiology File is necessary. For example, Pichon et al showed in their analyse of the French National Rare Disease Registry that 228 rare diseases have a higher prevalence in France than demonstrated by the Orphanet Epidemiology File.…”
Section: Codingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a more comprehensive coding for inpatients represents an important step towards obtaining improved epidemiological data on rare diseases. 5,13 It would be interesting to determine whether the prevalence data from the Orphanet Epidemiology File aligns with the coded cases of rare diseases or whether an update to the Epidemiology File is necessary. For example, Pichon et al showed in their analyse of the French National Rare Disease Registry that 228 rare diseases have a higher prevalence in France than demonstrated by the Orphanet Epidemiology File.…”
Section: Codingmentioning
confidence: 99%
“…The Alpha-ID-SE is updated and extended annually by the German Federal Institute for Drugs and Medical Devices (BfArM). 5…”
Section: Icd-10mentioning
confidence: 99%
“…Choquet et al 21 : LORD, 2. Kretschmer et al 15,16 : Parameterized form at the Dresden University Hospital 3. Martin et al 15 : Parameterized form at the Würzburg University Hospital 4.…”
Section: Research Question Extracted Informationmentioning
confidence: 99%
“…An obligation to document rare diseases with ORPHAcode and the German Alpha-ID-SE is mandatory since 2023. 14,15 However, few approaches have been published on how to integrate the specific coding systems into clinical practice and IT infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Това прави получаването на информацията за заболеваемост, болестност, оценка на необходимостта от здравни ресурси и тяхното планиране за РБ трудна. Номенклатурата, разработена от международната референтна база данни за редки болести Orphanet, позволява ясното им кодиране с помощта на така наречените ORPHA кодове [9,10]. Orphanet е създадена през 1997 г. във Франция с цел събиране на данни, подобряване на лечението и диагностицирането на РБ.…”
Section: въведениеunclassified